2020
DOI: 10.1108/jhr-09-2019-0214
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality among type 2 diabetes mellitus patients in a private hospital setting in Yangon, Myanmar

Abstract: PurposeThis study aimed to assess the sleep quality and its associated factors among patients with type 2 diabetes mellitus (T2DM) in a private hospital in Yangon, Myanmar.Design/methodology/approachA cross-sectional study was conducted. A total of 289 T2DM patients were interviewed using a structured questionnaire. An English version of the Pittsburgh Sleep Quality Index (PSQI) was translated into Myanmar and used for assessing sleep quality.FindingsApproximately 48.4% of T2DM patients had poor sleep quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
(76 reference statements)
3
1
1
Order By: Relevance
“…The PSQI score average was 7.5±3.44. This result was in line with the study by Htut NH et al, 8 which found that 48.4% of participants had poor sleep quality. In a similar vein, 51.9% of the study participants had poor sleep quality, according to Obaid ZH et al 9 Similarly, the mean PSQI score of 7.5±3 reported by Gozashti MH et al 10 was in line with the outcomes of our investigation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The PSQI score average was 7.5±3.44. This result was in line with the study by Htut NH et al, 8 which found that 48.4% of participants had poor sleep quality. In a similar vein, 51.9% of the study participants had poor sleep quality, according to Obaid ZH et al 9 Similarly, the mean PSQI score of 7.5±3 reported by Gozashti MH et al 10 was in line with the outcomes of our investigation.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings were supported by the significant statistical difference (p = 0.004) in sleep quality between the two groups. Our findings also aligned with the research carried out by Htut NH et al, 8 ) Sakamoto R et al's findings from 2013 were comparable. Similarly, Martorina W. 14 and others discovered that, with a p value of less than 0.001, low sleep quality is linked to poor glycemic management.…”
Section: Association Of Sleep Quality [Psqi] With Glycemic Controlsupporting
confidence: 93%
“…The finding of this study was consistent with the studies conducted in China (47.1%) ( 44 ), Thailand (48.4%) ( 45 ), and Myanmar (48.4%) ( 45 ). The possible justification could be that diabetic patients may have similar physiological complications such as nocturia, nocturnal hypoglycemia, restless leg syndrome, sedentary breathing, and diabetic and heart failure problems.…”
Section: Discussionsupporting
confidence: 92%
“…The proportion of individuals with T2DM who had low sleep quality was 81% in Jordan, 13 80% in the United States, 42 77.4% in Turkey, 43 and 72% in Saudi Arabia. 44 The proportions in this study are higher than those of studies conducted in Kenya with 53.4%, 45 48.4% in Myanmar, 46 63.9% in Trinidad and Tobago, 47 and 63.3% in Thailand. 48 Moreover, a significant proportion of 87.5% of individuals with T2DM reported that they typically take >15 minutes to fall asleep each night.…”
Section: Discussioncontrasting
confidence: 72%